Does government linked companies (GLCs) perform better than non-GLCs? evidence from Malaysian listed companies - Ab Razak, Nazrul Hisyam; Ahmad, Rubi; Ahmed, Huson Joher Ali (International Scientific Press, 2011)
The purpose of this paper is to examine the impact of an alternative ownership/control structure of corporate governance on firm performance. Specifically, we investigated the governance system of government linked companied (GLCs) in Malaysia. In this paper, we examine governance mechanism and firm performance of Malaysian GLCs and non-GLCs over a 11 year period from 1995 to 2005. We only select a sample of companies which are listed in Main Board. We chose a sample of 210 firms. We used Tobin’s Q which is an indicator of market performance is used as a proxy for company’s performances; meanwhile ROA is used to determine accounting performance. . This paper is to determines whether after controlling firm specific characteristics such as corporate governance, agency cost, growth, risk and profitability, GLCs perform better than non-GLCs. Findings highlight that non-GLCs performance is better GLCs in term of corporate governance, and other firm specific characteristics. The relationship between ownership structure and firm performance has been issue of interest among academics, investors and policy makers as one of key issues in understanding the effectiveness of alternative governance systems where government ownership serves as a control mechanism.